2014
DOI: 10.1007/s12026-014-8529-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of multiple sclerosis by CD8+ T cells

Abstract: The role of CD8+ T cells in the process of autoimmune pathology has been both understudied and controversial. Multiple sclerosis (MS) is an inflammatory, demyelinating disorder of the central nervous system (CNS) with an underlying T-cell-mediated immunopathology. CD8+ T cells are the predominant T cells in human MS lesions, showing oligoclonal expansion at the site of pathology. It is still unclear whether these cells represent pathogenic immune responses or disease-regulating elements. Through studies in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 86 publications
4
29
0
Order By: Relevance
“…These APCs can efficiently activate CNS-reactive CD4 and CD8 T lymphocytes. Different regulatory T lymphocyte subsets have been shown to reduce the development and severity of EAE (Kleinewietfeld and Hafler 2014;Sinha et al 2014). Several groups reported that regulatory T cell subsets from MS patients have impaired regulatory functions compared to healthy donors (Kleinewietfeld and Hafler 2014;Sinha et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These APCs can efficiently activate CNS-reactive CD4 and CD8 T lymphocytes. Different regulatory T lymphocyte subsets have been shown to reduce the development and severity of EAE (Kleinewietfeld and Hafler 2014;Sinha et al 2014). Several groups reported that regulatory T cell subsets from MS patients have impaired regulatory functions compared to healthy donors (Kleinewietfeld and Hafler 2014;Sinha et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding about the T cell-mediated immune processes that underlie MS pathogenesis and regulation has improved considerably over the past several years [14-17] However; the laboratory tests available for MS do not utilize this advanced level of knowledge. Diagnosis of MS still depends on a combination of radiographic, clinical and laboratory criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of Treg subtypes are now well recognized including thymic derived-nTregs, peripherally induced-iTregs, including Tr1 regulatory cells [21, 22], Th3 cells [23, 24] and CD8 + Tregs [19, 20, 25, 26]. Impaired immunosuppression by iTregs, including Tr1 cells or induced CD8 + Tregs has been associated with MS [27, 28].…”
Section: Resultsmentioning
confidence: 99%